Sleep disorders in correctional officers: cross-sectional study - Bezerra, Glécia Lemos; Carvalho, Fernando Martins; Fernandes, Rita de Cássia Pereira; Santos, Kionna Oliveira Bernardes (Sleep Science, 2022)
Introduction: Within the prison environment, where strict surveillance and prompt decision-taking are essential to maintain security, poor sleep may be hazardous to correctional officers. This study aims to estimate the prevalence of and identify factors associated with severe sleep disorders in correctional officers.Material and Methods: An exploratory cross-sectional study comprised all correctional officers in a prison complex in Salvador city, Brazil. Information about sleep quality, sociodemographic and occupational aspects, lifestyle habits, and common mental disorders (self-reporting questionnaire-20 score ≥7 points) were collected via a self-administered questionnaire. Severe sleep disorder was defined as a score ≥31 points according to the mini sleep questionnaire. The measure of association used was the prevalence ratio (PR). Prevalence ratios were estimated by using a Cox multivariate regression model. The final adjusted model only included the variables that presented a prevalence ratio ≥1.20.Results: The prevalence of severe sleep disorders in the 374 correctional officers was 55.3%, and was strongly (prevalence ratio ≥1.20) associated with number of stressful activities at work (RPs=1.24, 1.19, and 1.17), number of attack and threat events against the correctional officers over the last 12 months (RPs showing gradient, 1.11, 1.24, and 1.41), common mental disorders (RP=2,24), and non-White skin color (RP=1,37).Conclusion: This study found high prevalence of severe sleep disorders in correctional officers, associated with impairment of their mental health, skin color, and, particularly, with situations of stress and violence at work. These factors must be taken into account when planning and providing health care to these workers.
Keywords: Sleep; Prisons; Working Conditions; Violence; Mental Health